CADETS’ PERCEPTION OF LEARNING MANAGEMENT SYSTEM - Wisnu Risianto; Markus Asta Patma Nugraha; Rizka Maulia Adnansyah (Jurnal Pendidikan (Teori dan Praktik), 2024)
This study aims to assess the perceptions of cadets regarding the Learning Management System Platform so that its implementation is more optimal and can be implemented comprehensively and completely. This study uses a qualitative descriptive research method. In this study, the number of cadets sampled was 85 respondents or 49% of the population using a random sampling technique. The data collection technique used in this study was the questionnaire technique. The result of the study shows that it can be concluded that the cadets of the West Sumatra Maritime Polytechnic have a good perception of the Learning Management System. The Learning Management System can be used as an online learning management platform.